Proceedings of the ACM Web Science Conference 2015
DOI: 10.1145/2786451.2786460
|View full text |Cite
|
Sign up to set email alerts
|

How much is Wikipedia Lagging Behind News?

Abstract: Wikipedia, rich in entities and events, is an invaluable resource for various knowledge harvesting, extraction and mining tasks. Numerous resources like DBpedia, YAGO and other knowledge bases are based on extracting entity and event based knowledge from it. Online news, on the other hand, is an authoritative and rich source for emerging entities, events and facts relating to existing entities. In this work, we study the creation of entities in Wikipedia with respect to news by studying how entity and event ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…whether a word represents negative emotion. Since a word may be in function of different LIWC categories, we chose the most descriptive LIWC category for a word 8 . In general, LIWC categories express a range of psychological and sociological functions of words, and thus, are highly important for subjective tasks like detecting statements with biased language.…”
Section: Statement Representationmentioning
confidence: 99%
“…whether a word represents negative emotion. Since a word may be in function of different LIWC categories, we chose the most descriptive LIWC category for a word 8 . In general, LIWC categories express a range of psychological and sociological functions of words, and thus, are highly important for subjective tasks like detecting statements with biased language.…”
Section: Statement Representationmentioning
confidence: 99%
“…An investigation of external references from entity pages within English Wikipedia pages (2001)(2002)(2003)(2004)(2005)(2006)(2007) found that 20% were to news articles (Fetahu, Anand, & Anand, 2015). An investigation of external references from entity pages within English Wikipedia pages (2001)(2002)(2003)(2004)(2005)(2006)(2007) found that 20% were to news articles (Fetahu, Anand, & Anand, 2015).…”
Section: Citations To News Storiesmentioning
confidence: 99%
“…Although there are relatively few scholarly citations to newspapers, encyclopedia citations to news stories seem to be more frequent. An investigation of external references from entity pages within English Wikipedia pages (2001)(2002)(2003)(2004)(2005)(2006)(2007) found that 20% were to news articles (Fetahu, Anand, & Anand, 2015).…”
Section: Citations To News Storiesmentioning
confidence: 99%
“…This is problematic when dealing with long-tail entities, entities not prominent enough to be included in general domain KBs yet important for domainspecific search tasks, e. g. patent search or historical search [25]. The problem is equally acute with emerging entities, i. e. entities that are completely new or are just gaining popularity, as it often takes considerable time for entities to be added to a KB [16,7].…”
Section: Motivationmentioning
confidence: 99%